1977
DOI: 10.1590/s0006-87051977000100011
|View full text |Cite
|
Sign up to set email alerts
|

Melhoramento do cafeeiro: XXXVII - Observações sobre a resistência do cafeeiro ao bicho-mineiro

Abstract: Diversos cultivares, híbridos e retrocruzamentos no gênero Coffea foram, avaliados, em condições de campo, quanto à resistência ao ataque pelo bicho-mineiro. Entre as espécies diplóides observou-se acentuada variabilidade quanto ao grau de infestação. As espécies C. eugenioides, C. dewevrei, C. racemosa, C. liberica, C. kapakata apresentaram reduzida porcentagem de folhas atacadas, enquanto C. stenophylla mostrou-se praticamente imune. As espécies C. canephora e C. congensis revelaram-se suscetíveis. Altos índ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

1984
1984
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 1 publication
1
18
0
3
Order By: Relevance
“…For instance, the damage observed in C. canephora cv. Robusta, either at field natural infestations (Medina-Filho et al 1977), or at artificial laboratory conditions (Guerreiro-Filho et al 1991), is very severe and similar to that verified in C. arabica cultivars. However, infestations in fields of C. canephora cv.…”
Section: Introductionsupporting
confidence: 77%
“…For instance, the damage observed in C. canephora cv. Robusta, either at field natural infestations (Medina-Filho et al 1977), or at artificial laboratory conditions (Guerreiro-Filho et al 1991), is very severe and similar to that verified in C. arabica cultivars. However, infestations in fields of C. canephora cv.…”
Section: Introductionsupporting
confidence: 77%
“…Values indicate the mean of the replicate samples ( §SD) It is noteworthy that previous studies have reported that after insect oviposition, plants can avoid egg development by producing punctiform necrotic lesions surrounding the egg deposition sites, resembling a HR (Shapiro and Devay 1987;Balbyshev and Lorenzen 1997;Little et al 2007). A similar phenotype was detected at the oviposition site of L. coVeella larvae in highly resistant coVee plants (Medina-Filho et al 1977;Guerreiro-Filho et al 1991;Mondego et al 2005). The MLP tumour-related protein NF34 elicited HR in the tobacco mosaic virus (TMV)-susceptible tobacco plants, when over-expressed by a TMV expression vector (Karrer et al 1998), and an Arabidopsis Kunitz trypsin inhibitor (AtKTI1) that is similar to the MLPs was shown to be a modulator of plant pathogen-related PCD (Li et al 2008).…”
Section: Implications Of Comir Expression In Plant Development and Stmentioning
confidence: 56%
“…half of the leaves observed with mines present less than 25% of the total leaf area damaged by the mine. Coffea (Medina-filho et al, 1977) is one example of plant-insect interaction being negative to the plant. the Coffea species are susceptible to the leafminer Leucoptera coffeella, which is responsible for production losses because the premature leaves fall and there is consequent reduction of the photossynthetic area (Magalhães, 1964).…”
Section: Discussionmentioning
confidence: 99%